A Legal Review about “Demi Kita Program”: The Concept and Its Application for Indonesia Families - Bahrudin, Nurbaiti; Purnamasari, Linda; Putriani, Ananda; Hapsari, Nia Puspita; Sajali, Munawir (Law Development Journal, 2024)
"Demi Kita" is the first edu-web platform or portal in Indonesia that focuses on empowering and strengthening the capacity of prospective couples and families to have the spirit of continuous learning. This research aims to conduct an in-depth study related to the concept of the "Demi Kita" program as an effort to strengthen family institutions. After that, the description related to the "Demi Kita" program is reviewed using a normative or legal approach. The type of research used in this study is Normative Legal Research with a legal approach (based on norm research). The data collection techniques used in this study are interviews and documentation. In addition, the researcher used literature studies. The data analysis used in this study is a qualitative descriptive analysis. The results of this study inform that “Demi Kita” is the first edu-web platform or portal in Indonesia that focuses on empowering and strengthening the capacity of prospective couples and families to have the spirit of continuous learning. The use of the latest technology is used to increase the effectiveness of the program in supporting family education. The goals and programs of “Demi Kita” are in accordance with the purpose of marriage, which is to form a happy and eternal family. As according to the marriage law and several legal scholars related to the meaning of marriage. In addition, marriage law in Indonesia, along with related regulations, provides a strong basis to support programs for our sake. Namely lifelong education for families, increasing family capacity, establishing partnerships in family planning programs, and improving the skills of extension workers and field officers.